2021
DOI: 10.1021/acs.jmedchem.1c00296
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Peptides that Selectively Inhibit the Mycobacterium tuberculosis Proteasome

Abstract: Treatment of tuberculosis (TB) currently takes at least 6 months. Latent Mycobacterium tuberculosis (Mtb) is phenotypically tolerant to most anti-TB drugs. A key hypothesis is that drugs that kill nonreplicating (NR) Mtb may shorten treatment when used in combination with conventional drugs. The Mtb proteasome (Mtb20S) could be such a target because its pharmacological inhibition kills NR Mtb and its genetic deletion renders Mtb unable to persist in mice. Here, we report a series of macrocyclic peptides that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Centrally important to this pathway is the interaction of the AAA unfoldase Mpa with the 20S CP and the recruitment of protein substrates marked by pupylation for degradation by this molecular machine. Despite the significance of this complex as a drug target 44 , structural information on the fully assembled, active protease has been lacking. Our high-resolution cryo-EM structure of the substrate-engaged Mpa–proteasome complex reveals the dynamic character of the interaction between the AAA unfoldase ring and the proteasome core cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…Centrally important to this pathway is the interaction of the AAA unfoldase Mpa with the 20S CP and the recruitment of protein substrates marked by pupylation for degradation by this molecular machine. Despite the significance of this complex as a drug target 44 , structural information on the fully assembled, active protease has been lacking. Our high-resolution cryo-EM structure of the substrate-engaged Mpa–proteasome complex reveals the dynamic character of the interaction between the AAA unfoldase ring and the proteasome core cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome inhibitor drugs revolutionized the treatment of multiple myeloma, which once was untreatable before the approval of bortezomib in 2003 . Since then, this barrel-shaped, ATP-dependent, compartmentalized, and highly regulated N-terminal threonine hydrolase has emerged as viable targets for drug development against tuberculosis, malaria, leishmaniasis, and Chagas’ disease. The very active field of studies offers hope that selective pathogens’ proteasome inhibitors will one day be targeted clinically for the treatment of infectious diseases. Its potential as antimalarial drug target is particularly attractive as the pharmacological inhibition of its function is detrimental to the viability of the parasites at multiple stages of its life cycle, and its synergy with artemisinin, which is the core component of the artemisinin combination therapy of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma stability of the compounds was determined as previously reported . The human plasma was ordered from Sigma-Aldrich (H3667).…”
Section: Methodsmentioning
confidence: 99%
“…Macrocycle TDI5575 was developed using a strategy to covalently link the P2 and P4 phenyl groups of DPLG2 ( Fig 3 and Table 1 ) [ 46 ]. S2 and S4 binding pockets are partially exposed to solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The co-crystal structure of Mtb20SOG with TDI5575 showed that the bulky 2-phenyl substituent on the pyrrolidinyl of the P3-Asn binds to the shallow but wide S3 pocket, affording strong species selectivity. Treating Mtb with TDI5575 led to the accumulation of Pup-tagged GFP and to death of nonreplicating Mtb under NO stress [ 46 ].…”
Section: Introductionmentioning
confidence: 99%